Pamali Sebagai Sarana Pelestarian Keadilan Sosial dalam Budaya Lokal di Desa Karyamukti - Jannah, Tsani Syabirah Nur; Revana , Alya; Fitri, Mutiara Nur; Ramadani, Salwa Nuzila; Shidqiyah, Shafa Firda; Fitria, Ratna (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This research aims to examine the role of pamali as a form of local wisdom in supporting the value of social justice in Karyamukti Village. Using a descriptive qualitative approach, this study explores the meaning of pamali for the community, its application in daily life, and how this tradition adapts amidst the influences of modernization. Data was collected through interviews, observations, and documentation studies, and then analyzed using thematic analysis techniques. The research findings show that pamali still functions as a social control tool that maintains harmony and order among the community. Although globalization influences the views of the younger generation, the values of pamali remain relevant and can be adapted in the current context. These findings affirm that pamali is not only a cultural heritage but also plays a role in shaping the character and social life of the community.